2019
DOI: 10.31718/mep.2019.23.5-6.07
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Quercetin and Epigallocatechin-3-Gallate as Agents to Prevent Connective Tissue Disintegration in the Periodontium of Rats Under Systemic and Local Administration of Lipopolisaccharide of Salmonella Typhi

Abstract: The aim of the present study was to investigate the co-effect produced by water-soluble form of quercetin and epigallocatechin-3-gallate (EGCG) on biochemical markers of periodontal organic matrix depolimerization under systemic administration and local application of S. typhi lipopolisaccharide (LPS). The studies were conducted on 30 white rats of the Wistar line weighing 180-220 g, divided into 5 groups: the 1st included intact animals, the 2nd was made up of animals after the combined systemic and local LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…3 ). This inhibition leads to a reduction in oxidative-nitrosative stress in various organs, as indicated by research findings [ [80] , [81] , [82] , [83] , [84] ]. The activation of NF-κB is responsible for the upregulation of a number of genes encoding pro-oxidant and pro-inflammatory proteins, such as gp91 phox, xanthine oxidoreductase, cyclooxygenase 2, lipoxygenase 5 and 12, monooxygenases Cyp7b, Cyp2E1, Cyp2C11, inducible and neuronal isoforms of NO synthase, histolytic enzymes such as collagenase, stromelysin, gelatinase B, among others [ 85 , 86 ].…”
Section: Antioxidant Anti-inflammatory and Anti-diabetic Effectsmentioning
confidence: 94%
“…3 ). This inhibition leads to a reduction in oxidative-nitrosative stress in various organs, as indicated by research findings [ [80] , [81] , [82] , [83] , [84] ]. The activation of NF-κB is responsible for the upregulation of a number of genes encoding pro-oxidant and pro-inflammatory proteins, such as gp91 phox, xanthine oxidoreductase, cyclooxygenase 2, lipoxygenase 5 and 12, monooxygenases Cyp7b, Cyp2E1, Cyp2C11, inducible and neuronal isoforms of NO synthase, histolytic enzymes such as collagenase, stromelysin, gelatinase B, among others [ 85 , 86 ].…”
Section: Antioxidant Anti-inflammatory and Anti-diabetic Effectsmentioning
confidence: 94%
“…According to our data, the combination of inhibitors of NFκB- or AP1 activation and Nrf2/ARE inducers appears as more effective means to correct SIR and general metabolic disorders that has been evidenced by an example of the combined use of ammonium pyrrolidinedithiocarbamate and quercetin as NFκB inhibitors and SR 11302 as an AP1 inhibitor, and epigallocatechin-3-gallate as an Nrf2/ARE inducer [ 88 , 89 ]. Due to their combined action, the above compounds prevent the production of secondary byproducts of lipid peroxidation in the blood of rats, enhance the antioxidant potential, correct carbohydrate metabolism disorders (hyperinsulinaemia, insulin resistance), as well as restrain oxidative-nitrosative stress and depolymerization of collagenous and non-collagenous components of the periodontal organic matrix more effectively compared with the separate administration of the compounds.…”
Section: Role Of the Redox And Oxygen-sensitive Transcription Factors...mentioning
confidence: 99%
“…The experiment on white rats showed that the combined use of EGCG and quercetin in LPS-induced SIR significantly suppressed the development of oxidative-nitrosative stress in the periodontal tissues of rats by reducing the ROS/RNS production that was accompanied by the improvement in the functional state of the periodontium [ 89 ]. In the other study, the authors emphasize the role of the combined effect of EGCG and quercetin in restraining depolymerization of periodontal extracellular matrix proteins (collagen, proteoglycans, and glycoproteins) under the conditions of LPS administration [ 88 ]. The series of experimental works confirm the expediency of combining water-soluble form of quercetin and SR 11302, an inhibitor of AP1 transcription factor, under LPS-induced SIR [ 220 ], as well as with metformin, which is able to suppress the NFκB activation under water avoidance stress [ 221 ].…”
Section: Polyphenols As Regulators Of Transcription Factorsmentioning
confidence: 99%
“…Таким чином, наше дослідження підтверджує розвиток морфологічних ознак пародонтиту, які проявляються, в першу чергу, запаленням і деструкцією періодонта, формуванням патологічної періодонтальної кишені, деструктивними змінами в кістковій тканині альвеолярного відростка і в цементі кореня зуба. Це у повній мірі узгоджується з раніше виявленими метаболічними та структурними розладами у пародонті за таких самих умов експерименту: розвитком окиснонітрозативного стресу, деполімеризацією сполучної тканини пародонта (колагену, протеогліканів, сіалоглікопротеїнів), збільшенням коефіцієнту оголення коренів молярів [8,9,15]. Пригнічення NF-κB та індукція сигнального шляху Nrf2 -ARE обмежує реалізацію цих механізмів пошкодження пародонта, що попереджує розвиток морфологічних ознак пародонтиту, Висновки 1.…”
Section: результати дослідження та їх обговоренняunclassified
“…Іншим підходом є індукція сигнальних систем, що виявляють функціональний антагонізм до наведених вище транскрипційних чинників, зокрема шляху Keap1 / Nrf2, який активує експресію генів за рахунок взаємодії транскрипційного фактора Nrf2 з цис-регуляторним енхансером, ві-домим як антиоксидант-респонсивний елемент (ARE). Так, введення поліфенолу епігалокатехін-3-галату (epigallocatechin-3-gallate -EGCG), механізм дії якого реалізується через активацію Nrf2 внаслідок протеолізу інгібіторного білка Keap1 [7], істотно зменшує у тканинах пародонта генерацію активних форм оксигену, знижує сумарну активність NO-синтази та концентрацію пероксинітриту [8], обмежує деградацію органічного матриксу [9].…”
unclassified